2020
DOI: 10.1016/j.jallcom.2020.156633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen on mechanical properties of CoCrFeMnNi high entropy alloy at room and cryogenic temperatures

Abstract: Specimens of a CoCrFeMnNi high entropy alloy with different content of nitrogen (0.5e2.0 at.%) were prepared by induction melting. Microstructure and tensile mechanical behavior of the alloys in the ascast condition were analyzed. The alloys with a low amount of N (0.5e1.0 at.%) had a single fcc phase coarse-grained microstructure. An increase in the content of N to 2.0 at.% resulted in the precipitation of a small amount (~1%) of Cr-rich M 2 N nitride particles. The yield strength of the alloys increased in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(29 citation statements)
references
References 76 publications
5
24
0
Order By: Relevance
“…This result is in agreement with the fact that, at this scale of observation, no primary precipitation was observed in any sample. This also indicates that cooling down to room temperature, which takes only a few minutes after solidification, is not long enough to provoke the precipitation of low temperature phases predicted at equilibrium, like Cr 2 N or , for instance in agreement with the observations of Klimova et al [26].…”
Section: Phase Stability In the N-doped Y3 Grade : Thermodynamic Predictionsupporting
confidence: 87%
See 3 more Smart Citations
“…This result is in agreement with the fact that, at this scale of observation, no primary precipitation was observed in any sample. This also indicates that cooling down to room temperature, which takes only a few minutes after solidification, is not long enough to provoke the precipitation of low temperature phases predicted at equilibrium, like Cr 2 N or , for instance in agreement with the observations of Klimova et al [26].…”
Section: Phase Stability In the N-doped Y3 Grade : Thermodynamic Predictionsupporting
confidence: 87%
“…It should however be noted that nitride precipitation kinetics is believed to be relatively slow compared to carbide precipitation [30] explaining why Cr 2 N is nearly never observed in the as-cast state of a nitrogen-doped Cantor alloy. Klimova et al [26] showed that for a Cantor alloy doped with 0.22 wt. % N (0.88 at.…”
Section: Phase Stability In the N-doped Y3 Grade : Thermodynamic Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mukhtar et al [ 24 ] show that nitriding as the thermo-chemical treatment can improve wear resistance and surface hardness and reduce the fatigue life of AM Ti64 compared to AM Ti64 subject to the same thermal treatment without nitriding. Klimova et al [ 25 ] studied the effect of nitrogen (0.5–2.0 at.%) on the structure and mechanical properties of CoCrFeMnNi high entropy alloy as-cast condition. They showed that increase in the N content to 2.0 at.% resulted in the precipitation of a small amount (<1%) of the Cr-rich M 2 N nitride particles at the face-centered cubic (FCC) grain boundaries.…”
Section: Introductionmentioning
confidence: 99%